Teaching Software Engineering: An Overview of Current Approaches and Practices in the Last Decade of SBES - Clementino, Ana; Lima, Erick; Lima, Luann; Guedes, André; Netto, Dorgival; Coutinho, Jarbele (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3517, 2024)
Software Engineering is constantly evolving, with new tools and programming languages fluctuating in popularity over time. However, the curriculum of Software Engineering disciplines cannot keep up with these innovations and remain current. On the other hand, if the courses promote constant adaptation of the teaching of the subject to keep it in line with updates, this may result in a misaligned curriculum. Therefore, it is necessary to have an indepth understanding of successful practices, the challenges faced, and the opportunities that may arise in this process. Based on this understanding, this paper presents a bibliographic study of the Brazilian Symposium on Software Engineering (SBES) over the last ten years (2013 to 2023) with the main objective of investigating the approaches currently used to promote teaching areas that include Software Engineering. In this way, 48 papers were identified that aim to answer the questions investigated. Finally, the intention is, based on the best practices measured, to develop a strategic model that can serve as a guide for identifying existing approaches.